LINTAS-LC 1.1: Model dan Simulasi Jalur Lingkar Cileunyi Menggunakan SimEvents MATLAB - Erwin Harahap; Farid H Badruzzaman; Deni Darmawan (Prosiding SISFOTEK, 2019)
The smooth flow of traffic is one of the parameters of controlled transportation system management. As the population grows, traffic becomes more congested and causes congestion in various locations. One of the locations of congestion of national concern is the Cinunuk road that connects the Cibiru Roundabout to Cileunyi (BCC). The BCC is located in the Cibiru and Cileunyi sub-districts, the border of the City and Regency of Bandung. The congestion starts at the Cibiru roundabout and continues along the Cinunuk highway to the one-way intersection for each lane. BCC is the only Non-Toll road that connects traffic in northern West Java to the south and east coast via the city of Bandung. This condition results in high flow of vehicles that pass through the lane so that congestion occurs every day from morning to night. One alternative solution to unravel this congestion problem is to build a new alternative path known as the Cileunyi Circle (LC). This article discusses the study of traffic situations at BCC locations with LC alternatives through mathematical modeling methods and simulations. The application used for simulation is MATLAB-SimEvents on the basis of the queue model.